A Model for Diversification - Ansoff, H. I. (Management Science, 1958)
During the past few years, many interesting papers have been written on the subject of product-market diversification. A majority of the writers have dealt with either case histories of successful diversification or with qualitative check-off lists to be used in analyzing specific diversification opportunities. A much smaller group of papers has been devoted to formulation of a systematic approach which a company can use to compare alternative diversification decisions. This paper falls in the latter category. As a first step, diversification is defined and distinguished from other company growth alternatives. Typical growth perspectives are described which may motivate a company to diversify. Diversification objectives are established and related to the company's long-range objectives. A two-step evaluation scheme is proposed for selection of the preferred diversification strategy. The first is a qualitative step, which narrows a wide field of diversification opportunities to a selected few which are consistent with the company's diversification objectives and long-range policy. In the second step, a quantitative procedure is outlined for evaluating the relative profit potential of the selected alternatives. Finally, limitations of the present method are discussed.